2009
DOI: 10.1128/aac.01146-08
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Activity of Antibiotics in a Model of Human THP-1 Macrophages Infected by a Staphylococcus aureus Small-Colony Variant Strain Isolated from a Cystic Fibrosis Patient: Study of Antibiotic Combinations

Abstract: In a companion paper (H. A. Nguyen et al., Antimicrob. Agents Chemother. 53:1434-1442, 2009), we showed that vancomycin, oxacillin, fusidic acid, clindamycin, linezolid, and daptomycin are poorly active against the intracellular form of a thymidine-dependent small-colony variant (SCV) strain isolated from a cystic fibrosis patient and that the activity of quinupristin-dalfopristin, moxifloxacin, rifampin, and oritavancin remains limited (2-to 3-log CFU reduction) compared to their extracellular activity. Antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
24
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 27 publications
6
24
1
1
Order By: Relevance
“…The postphagocytosis inoculum was typically 1.0 to 2.5 ϫ 10 6 CFU per mg of cell protein. As discussed previously (33), the large dilution of samples before spreading on agar plates for CFU counting ensured the absence of a carryover effect. To further check for the absence of a carryover effect, we examined the capacity of cell lysates obtained from cells incubated with delafloxacin to impair the growth of S. aureus ATCC 25923.…”
Section: Methodsmentioning
confidence: 99%
“…The postphagocytosis inoculum was typically 1.0 to 2.5 ϫ 10 6 CFU per mg of cell protein. As discussed previously (33), the large dilution of samples before spreading on agar plates for CFU counting ensured the absence of a carryover effect. To further check for the absence of a carryover effect, we examined the capacity of cell lysates obtained from cells incubated with delafloxacin to impair the growth of S. aureus ATCC 25923.…”
Section: Methodsmentioning
confidence: 99%
“…(Baltch et al, 2008). Nguyen et al (2009b) also showed additive or synergistic effects between oritavancin, moxifloxacin and rifampicin against intracellular SCVs.…”
Section: Enhancing Preexisting Antimicrobial Therapiesmentioning
confidence: 99%
“…Most antibiotics tested caused a reduction of bacterial counts, whereas all drugs showed higher intracellular activity against normal than against SCV strains (133). The authors also used their infection model to test antibiotic combinations with rifampin or oritavancin against intracellular SCVs, and they achieved a further decrease of the intracellular bacterial growth (135). Finally, concentration-dependent testing revealed that maximal efficacies of antibiotics were similar against wild-type and SCV strains, despite their different modes of infection (136).…”
Section: Susceptibility Testingmentioning
confidence: 99%